Ministry of Trade and Industry Decree No. 682 For The Year 2010 Concerning Modifying The Rates of Charge Of Services Carried Out By The Egyptian Authority For Export and Import Control = وزارة التجارة والصناعة قرار رقم 682 لسنة 2010 فى شأن تعديل بعض فئات مقابل الخدمات الى تقوم بها الهيئة العامة للرقابة على الصادرات والواردات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.